Ischemic diabetic retinopathy as a possible prognostic factor for chronic kidney disease progression - Lee, W J (Nature Publishing Group, 2014)
PURPOSE: To assess the value of diabetic retinopathy (DR) severity as a possible predictive prognostic factor for the progression of chronic kidney disease (CKD). PATIENTS AND METHODS: Retrospective cohort study. Patients (51) who were initially diagnosed with DR and CKD were enrolled and their medical records were evaluated. The following ophthalmic factors were assessed by fluorescein angiography at the initial visit: area of capillary nonperfusion, presence of neovascularization and vitreous hemorrhage, and DR grade. The effect of these factors on CKD progression over the 2-year period of the study, defined as doubling of serum creatinine or the development of end-stage renal disease requiring dialysis or renal transplant, was evaluated. RESULTS: The study included 51 patients with DR and CKD; of these, 11 patients (21.6%) were found to have proliferative DR (PDR) and seven patients (13.7%) had high-risk PDR at baseline. Patients with ischemic DR, who showed extensive capillary nonperfusion (≥10 optic disc areas) in the retina, had a greater risk for CKD progression (hazard ratio=6.64; P=0.002). CONCLUSION: We found that extensive capillary nonperfusion in the retina greatly increased the risk of progression of CKD in patients with DR. This suggests that the retina and the kidney may have shared risk factors for microvascular disease secondary to diabetes mellitus, and emphasizes the need for a team approach to diabetes care.